Pengaruh Pakan Limbah Tauge Dan Suplementasi Omega-3 Terhadap Produksi Spermatozoa Domba Garut - Nurcholis Nurcholis; Raden Iis Arifiantini; Mohamad Yamin (AGRICOLA, 2015)
The objective of the research was to analyze the feeding effect of bean sprout waste and omega-3 to the spermatozoa production  of garut rams. Twelve garut rams were divided into three groups of feeding; grass + concentrate (R1), bean sprouts waste + concentrate (R2)  and bean sprouts waste + concentrate + omega-3 (R3). The semen were collected by using artificial vagina once a week. Semen evaluated macroscopically              (volume, color, consistency and pH) and microscopically (mass movement, motility, viability, concentration, concentration per ejaculate and morphology of spermatozoa).The research was designed by using a completely randomized design (repeated measurement) and statistically analyzed using SAS 9.1 software. The results showed macroscopy no differences  was found on microscopyc evaluation except for semen volume. Microscopyc evaluation showed that motility, viability and spermatozoa concentration as well as total number per ejaculete feed with R2dan R3 were highger (P<0.05) than R1. However supplementation of omega-3 was no better than feed containing bean sprouts waste.